Determination of the DNA and amino acid sequences of the lactate dhydrogenase gene from plasmodium falciparum strains K1 and PF FCBR: A route to the design of new antimalarials - Balık, Dilek Turgut; Holbrook, J. John (My University, 2001)
This paper describes cloning of the gene coding for the lactate dehydrogenase (LDH) gene from the two different strains of Plasmodium falciparum, K1 and PF FCBR. The DNA sequences of LDH genes of these two strains were found to be identical. Amino acid sequence alignment of LDH from P. falciparum strains K1 and PF FCBR (PfLDH) to some other known LDH sequences showed that PfLDH has 29% residue identities with Bacillus stearothermophilus (BsLDH) and 29%, 31%, 33% with dogfish, man-M4, and pig-M4 LDHs, respectively. It was also shown that PfLDH has insertions and single amino acid deletions. Two deletions are glutamate-48 and glycine-217. It has a single amino acid insertion, a tyrosine, between residues 73 and 74, and most remarkably a five residue insertion in the catalytic loop compared to other LDH sequences. This five residue insertion could be exploited in drug design.
Keywords: DNA; Plasmodium falciparum; lactate dehydrogenase; nucleotide sequences; DNA cloning; amino acid sequences; antimalarials